2006
DOI: 10.1007/s11248-006-9046-y
|View full text |Cite
|
Sign up to set email alerts
|

A leaf-based regeneration and transformation system for maize (Zea mays L.)

Abstract: Efficient methods for in vitro propagation, regeneration, and transformation of plants are of pivotal importance to both basic and applied research. While being the world's major food crops, cereals are among the most difficult-to-handle plants in tissue culture which severely limits genetic engineering approaches. In maize, immature zygotic embryos provide the predominantly used material for establishing regeneration-competent cell or callus cultures for genetic transformation experiments. The procedures invo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
51
0
9

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(63 citation statements)
references
References 46 publications
3
51
0
9
Order By: Relevance
“…When starting with leaf-base explants, successful reports of transformation in maize have all relied on an intermediate callus-culture step to produce the transformable explant. For example, leaf bases in germinating maize seedlings have been used to produce callus for later transformation (Sidorov et al, 2006;Ahmadabadi et al, 2007). Importantly, we demonstrated here that mesophyll cells from maize seedlings can be directly transformed using Agrobacterium-mediated delivery of Bbm/ Wus2 and that those cells divide and appear to be the source of the embryogenic, regenerable callus produced in our experiments.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…When starting with leaf-base explants, successful reports of transformation in maize have all relied on an intermediate callus-culture step to produce the transformable explant. For example, leaf bases in germinating maize seedlings have been used to produce callus for later transformation (Sidorov et al, 2006;Ahmadabadi et al, 2007). Importantly, we demonstrated here that mesophyll cells from maize seedlings can be directly transformed using Agrobacterium-mediated delivery of Bbm/ Wus2 and that those cells divide and appear to be the source of the embryogenic, regenerable callus produced in our experiments.…”
Section: Discussionmentioning
confidence: 58%
“…However, to date, the closest researchers have come to directly using mature seed tissues for transformation in monocots has been a report in which a brief preculture period (1 to 5 d) was used before Agrobacterium-mediated DNA delivery in japonica rice (Toki et al, 2006). The remaining reports of "mature seed transformation" in monocots have all progressed through an intermediate culture step, using either embryogenic callus (Hiei et al, 1997;Chen et al, 1998;Dai et al, 2001;Sidorov et al, 2006;Ahmadabadi et al, 2007), organogenic callus (O' Connor-Sánchez et al, 2002) or proliferating meristem cultures (Zhong et al, 1996;Zhang et al, 2002), and finally using the proliferating cultured cells as the transformation target. Here, using the transcription factors Bbm and Wus2, we demonstrated that cells in the exposed embryo axis of mature maize seed can reproducibly produce transgenic callus and regenerate healthy, fertile T0 plants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Agrobacterium tumefaciens-mediated gene transformation has been established both for dicot (Block et al, 1984) and monocot (Hiei, 1994) plants and is hence being used for different crops such as wheat (Jones, 2005), maize (Ahmadabadi, 2007), rice (Hiei et al, 1994), and sugarcane (Enriquez et al, 2000). Poor regeneration of transformants is still a major barrier in crop improvement through genetic engineering (Popelka and Altpeter, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…옥수수 미성 숙 배로부터 식물체 재분화가 Green and Philips (1975)에 의 해 처음 보고된 이후로 다양한 품종의 미성숙 배로부터 식 물체 재분화 연구가 지속적으로 보고되었다 (Armstrong and Green 1985;Duncan et al 1985;Songstad et al 1988;Bohorova et al 1995;Carvalho et al 1997;El-Itriby et al 2003;Wang et al 2007;Binott et al 2008;Ombori et al 2008;Rakshit et al 2010;Anami et al 2010;De-yi et al 2011;González et al 2012;Ali et al 2014). 미성숙 배 외에도 성숙 배 (Wang 1987;Huang and Wei 2004;Al-Abed et al 2006;Abebe et al 2008;Jia et al 2008;Zhao et al 2008), 중배축(mesocotyl) 조직 (Torne et al 1980), 약 (Ting et al 1981), 유묘의 마디부분 (Santos et al 1984;Sidorov et al 2006), 잎 (Conger et al 1987;Ahmadabadi et al 2007), 영 (glume) (Suprasanna et al 1986), 화서(미성숙 tassel과 ears) 절 단 조직 (Pareddy and Petolino 1990;Songstad et al 1992), shoot-tip 분열 조직 (Li et al 2004)에서 캘러스 형성 및 식물체 재분화가 이루어졌다. 이렇게 옥수수의 여러 다양한 조직 으로부터 식물체 재분화가 이루어졌으나 지금까지 미성숙 배를 사용하였을 때 재분화 효율이 가장 높은 것으로 알려 져 왔다.…”
unclassified